Policy and Regulation in Digital Health - Allaudin, Fazilah Shaik (International Journal of Human and Health Sciences (IJHHS), 2019)
The dawn of the Fourth Industrial Revolution and the advances in telecommunicatio n are presenting multiple strategies and challenges ahead which includes policy and regulat ion, clinical evidence, safety and quality, medical ethics and clinical practice. However, these disruptions are also creating new opportunities to solve some of the biggest health-rela ted challenges facing the world today. The democratization of care and the great potential to health care offered by the digital revolution is the new paradigm embracing the delivery of care. The deployment of these new technologies and advances is progressing faster than regulator y framework can react. At the same time new technologies can deepen healthcare inequalities and unaffordability. Since 2018, efforts are underway by MOH to review and develop regulator y strategies and policies to foster digital health technologies, advocate translational research, spur innovations and boost the digital economy while at the same time, building an enabling ecosystem in Malaysia. New service models, technologies and innovations must be based on the principles of value-based, safety, quality, confidentiality, accountability and traceabilit y. The safe practice of digital health should keep the consumers of health care at the heart of the adoption. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 23